2015
DOI: 10.1111/ajd.12388
|View full text |Cite
|
Sign up to set email alerts
|

Sun‐protection practices among undergraduates at an Australian University

Abstract: Only a third of the sample practiced any method of sun protection and there were significant differences in the practices between subgroups, suggesting they were at an increased risk of sun damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
9
1
Order By: Relevance
“…Among the studies that provided medical students’ sex, nine studies reported a higher proportion of female medical students ( Awadh et al, 2016 , Bilushi et al, 2012 , Guile and Nicholson, 2004 ; Isvy et al, 2012; Jerkegren et al, 1998 , Purim and Wroblevski, 2014 , Rodriguez-Gambetta et al, 2016 , Scott et al, 2017 , Zuba et al, 2016 ). Furthermore, the mean age range of medical students in the nine studies that reported these data was 20.3 to 25.01 years ( Bilushi et al, 2012 , Gillani et al, 2001 , Jerkegren et al, 1998 , Patel et al, 2010 , Purim and Wroblevski, 2014 , Romani et al, 2005 , Shahnam et al, 2015 , Sweni et al, 2010 , Zuba et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Among the studies that provided medical students’ sex, nine studies reported a higher proportion of female medical students ( Awadh et al, 2016 , Bilushi et al, 2012 , Guile and Nicholson, 2004 ; Isvy et al, 2012; Jerkegren et al, 1998 , Purim and Wroblevski, 2014 , Rodriguez-Gambetta et al, 2016 , Scott et al, 2017 , Zuba et al, 2016 ). Furthermore, the mean age range of medical students in the nine studies that reported these data was 20.3 to 25.01 years ( Bilushi et al, 2012 , Gillani et al, 2001 , Jerkegren et al, 1998 , Patel et al, 2010 , Purim and Wroblevski, 2014 , Romani et al, 2005 , Shahnam et al, 2015 , Sweni et al, 2010 , Zuba et al, 2016 ).…”
Section: Resultsmentioning
confidence: 97%
“… Overall, the questionnaire revealed that both first- and sixth-year students’ knowledge of sunscreen, UV light, and skin cancer is deficient. • 52.5% used sunscreen only while at the beach • 17.5 % used sunscreen throughout the summer • 3.3% used sunscreen all the time (throughout year) • 50% of first-year students and 31% of sixth-year students used clothing, hat, and sunglasses Shahnam et al, 2015 ; Australia Questionnaire, n = 255 (science students, including medical students), mean age (medical students) = 22.7 (SD = 1.02) years Medical students’ data: • 80% used less than three sun-protection methods concurrently • 53% seek shade • 24% use sunscreen • 21% wear protective clothing • 3% wear a hat • 38% wear sunglasses Purim and Wroblevski, 2014 ; Brazil Questionnaire, n = 398 (72.1% have had attended discipline of dermatology, medical students: 20.1% first and second years, 59% third and fourth years, and 20.9% fifth and sixth years), 54.9% female, 87.4% White (color/race), mean age = 22.9 (SD = 3.1) years (range, 18-42 years) Not attended dermatology discipline: 30.6% knew ABCD rule and how to identify suspicious lesions Attended dermatology discipline: 69.6% knew ABCD rule and how to identify suspicious lesions • Sun exposure: 31.5% (between 10:00 a.m. and 4:00 p.m.) • Use sunscreen: Not attended dermatology discipline: 50% (summer) and 9.1% (daily); attended dermatology discipline: 49.1% (summer) and 8.1% (daily) • Use sunscreen: Only in summer (76.4% of men; 29.4% of women), daily (9.8% of men, 7.3% of women), during exercise (9.2% of men, 58.3% of women; p < .001) • SPF used in sunscreens: Not attended dermatology discipline (4.5% [< 15], 23.4% [15-25], 65.8% [> 30]), attended dermatology discipline (8.7% [< 15], 25.1% [15-25], 65% [> 30]) • Cap, visor or hat: Not attended dermatology discipline (5.4%), attended dermatology discipline (9.1%) • Sunglasses: Not attended dermatology discipline (48.6%), attended dermatology discipline (55%) • SSE: Not attended dermatology discipline (20.9%), attended dermatology discipline (61.1%) • Perform or have already performed tanning: 4.3% Awadh et al, 2016 ; Malaysia Questionnaire, n = 101 (final-year medical students), 63.4% female • 27.7-78.2% knew that sunscreen is effective in preventing sunburn, skin aging, skin cancer, enhancing a tan, and reversing aging signs • 31.7-92.1% knew sunscreen should be applied during sunny day, cloudy day, attending indoor activities, at night, and while swimming in the pool, beach, waterfall • 7.9-67.3% knew when and how often to apply sunscreen on sunny days/outdoors, amount of sunscreen to cover entire body, what SPF stands for, that sunscreen provides better protection when protection order is higher, and the risk of UV-A/B radiation • 7.9-34.7% had their sunscreen use influenced by friends, family, health care professionals, and others • 53.5% encouraged the use of sunscreen to others • 9.9% encouraged the use of sunscreen for babies < 6 months old • 40.6-79.2% agree that sunscreen is necessary to avoid the harmful effects of sun ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations